Upaya Pewarisan Tradisi Tarian Likurai Sebagai Salah Satu Bentuk Kearifan Lokal di Kabupaten Malaka - Clotilde Seran; Antonius Bere (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
This research is entitled Efforts to Inherit the Likurai Dance Tradition as a Form of Local Wisdom in Malacca Regency. The problems in this research are: 1) What are the values of Local Wisdom in the Likurai Dance in Malacca Regency?, 2) What are the Efforts to Inherit the Likurai Dance Tradition as a form of Local Wisdom in Malacca Regency? The aim of this research is to find out the values of local wisdom in the Likurai dance in Malacca Regency, and to find out efforts to inherit the Likurai dance tradition in Malacca Regency. The research method used in this research is a qualitative descriptive approach. Qualitative research. The results of the research show that the likurai dance is a dance that has long had a tradition of cutting off the heads of enemies so that when they returned from the battlefield, they always carried the enemy's head as a symbol of victory. However, after the independence era, the tradition of beheading was abolished, however the likurai dance is still being preserved today through efforts. The local wisdom values that exist in the people of Malacca Regency are strong evidence of the unity of the people of Malacca Regency so that they remain close in establishing relationships, especially for the sake of progress in preserving Malacca culture in the likurai dance. The process of passing on the Likurai dance tradition to the next generation has made this spirit of struggle continue to be developed so that what is instilled from Likurai continues to be visible to the faces of the new generation, not only as a form of dance but also the values contained in it.